Die Muttersprachenzählung von 1940 und die Zukunft der nichtenglischen Sprachen in den USA - Kloss, Heinz (ERDKUNDE, 1953)
In the U.S. Census of 1940 the mother-tongues of the entire white population, though only based on a 5 per cent, sample, were reported for the first and so far only time. Mother-tongue was defined as the principal language spoken in the home of a person during his earliest childhood. The proportion of Americans of American parentage (later referred to as „Altheimische) with a mother tongue other than English was highest among groups like the Spaniards of New Mexico and Colorado, the French of Louisiana and, to a lesser degree the Pennsylvania „Dutch (Germans), whose large language islands were created during the colonial period. This proportion took second place among those groups originated by immigrants from Mexico and Quebec after 1850, and minor language islands such as those created in the 19th century by the Norwegians in the Middle West, the Ger- mans in the Middle West and Texas, the Czechs in Texas and the Dutch in Michigan. The proportion was lowest among the descendants of post-1880 European immigrants, a group which has become completely urbanised. Thus Italian and Yiddish combined were the mother-tongues of 26 per cent, of the entire white „non-English population, but were only 6 per cent, of the „Altheimische; whereas of white persons who reported either French or Spanish as their mother-tongue the corresponding figures were 15 per cent, and 42 per cent., respectively. Thus French and Spanish appear to be emerging as the leading non- English languages in the United States.